Synthesis and properties of waterborne polyurethane dispersions for surface coatings on poly(vinyl chloride). (23rd July 2020) - Song, Sam Cha; Choi, Han Ho; Park, Kyung-Kyu; Park, Young Gwang; Lee, Seungjae; Im, Donghyeok; Lee, Won-Ki
Abstract: Recently, conventional solvent-typed polyurethanes are subject to many regulations due to emission of organic volatile compounds(VOCs) and researches have been focused on eco-friendly waterborne polyurethane dispersions(WPUDs) as an alternative of conventional solvent-typed ones causing poor working environment. PVC is widely used because of low price and good heat and fire resistance. To develop eco-friendly coatings on poly(vinyl chloride) (PVC), various WPUDs were synthesized by combination of polyol such as polyester, polycaprolactone, polyether or polycarbonate, hydrophilic compounds (dimethylol butanoic acid, DMBA), and reactive silicone. The structure and properties of synthesized WPUDs were characterized by FT-IR, particle size, contact angle, surface energy, tensile strength, elongation, and adhesion strength. Also, their particle sizes decreased while tensile strengths increased with increasing DMBA content. Surface energy and contact angle of WPUDs were strongly affected by the content of hydrophobic reactive silicone. The optimum properties of WPUDs were obtained by controlling their compositions, polyol, hydrophilic compound, and reactive silicone.